Primary Care Wound Clinics: A Qualitative Descriptive Study of Patient Experiences in Community Pharmacies - Lusi Sheehan; Sheldon Dias; Michael Joseph; Sahil Mungroo; Jake Pantinople; Kenneth Lee (MDPI AG, 2022)
The expansion of primary care wound services serves to alleviate secondary and tertiary care utilization. However, patient satisfaction is required to ensure service uptake. In recent years, various community pharmacies in Australia have begun to offer dedicated wound clinics; however, evaluations of patient experiences have yet to be conducted. Thus, the present study seeks to explore: (1) the experiences and satisfaction of patients who have received wound care consultations for their acute wounds in a community pharmacy setting; and (2) how current pharmacy-based wound services can be improved. Semi-structured individual interviews were conducted with patients across five pharmacy-based wound care clinics in Western Australia. Interviews were audio-recorded, transcribed verbatim, and imported into QSR NVivo 12 Plus. Interview transcripts were coded and thematically analyzed using the framework method. Twelve interviews were required to reach data saturation. Five key themes emerged: the accessibility of wound services, the comprehensiveness of wound care services, confidence in wound care consultants, the awareness and promotion of wound services, and the expansion of wound care services. Overall, participants were satisfied with the accessibility and comprehensiveness of pharmacy-based wound service delivery, trusted the health care providers, and wanted the service to be expanded. The reported patient satisfaction, confidence in the health care provider, and desire to expand the service suggests there is potential for the service to grow in Australia. Due to the growing costs of wound care globally, there is scope to further evaluate and expand wound care services in the primary care setting on an international level.